Penggabungan Citra Satelit Spot XS Dengan Foto Udara Pankromatik (Studi Kasus: Daerah Kodya Ba ndung) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRAK There are various methods for image fusion, i.e. RGB to HIS transformation, PCA, and Brovey. In this research, HIS and Brovey methods are implemented to merge aerial photograph and SPOT XS image. Firstly, aerial photograph and spOT XS imagery must be registered and cut to obtain an identical area in both images. SPOT XS image are resampled to aerial photograph to get spatial resolution which is equal to aerial photograph. In order to identify discrepancies between HIS fused image and Brovey's fused image, image differencing is needed. And, spectral and radiometric of fused images are evaluated using digital image classification. The research shows image fusion of aerial photograph and SPOT XS using both Brovey and HIS methods create new image that has spatial resolution equal with aerial photograph and spectral resolution equal with SPOT XS. By visual interpretation, image fusion using HIS method has better contrast rather than Brovey method. Image differencing shows there is radiometric discrepancies between fusion using HIS and Brovey methods. Meanwhile, the digital image classification's result are still not match with real condition. Key words: Citra satelit, foto Udara pankromatik